(3JMdjd hJUeje GdfXes - (3eMeO(B, (3GdUjQajs ((3GdGScfOQjI(B;(3GdbGgQI(B,(3eDSSI WjHI(B:s (3eDSSI MhQS GdOhdjI(B,s, 2005)
(3fXe GdeYdheGJ GdeMShHI, JMdjd fXe GdeYdheGJ, JUeje fXGe GdeYdheGJ JWHjb hGNJHGQ fXGe GdeYdheGJ(B.s
(3GdeQGLY U(B.215s
Keywords: (3JMdjd GdfXes; (3JcfhdhLjG GdeYdheGJs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s